KONSEP PEMIKIRAN ADIWARMAN AZWAR KARIM TENTANG ECONOMIC VALUE OF TIME DALAM SISTEM PERBANKAN - Ayu Mawaddatul Hakekah; M Mukhlis (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2023)
The purpose of this study is to find out how adiwarman azwar karim thinks about the concept of economic value of time and how the concept of economic value of time is in an Islamic perspective and its relevance in today’s economy. This type of research is qualitative in nature and is a library research with the primary source being the book by adiwarman azwar karim, namely Islamic macroeconomics (2017).secondary sources are studied from books other than the original figures, journals, websites and articles. The result of the study concluded that the concept of economic valoue of time according to adiwarman azwar karim is a concept where time has economic value, not money which has time value. Adiwarman karim’s concept of economic value of time is a rebuttal to the time value of money system, in which the concept of economic value of time is based on standardized calculations of money and money with no added value. Meanwhile, the time value of money directs people to the value of the benefits of money for money with added value (usury). In the perspective of sharia economic law, the concept of economic value of time is more acceptable than the concept of time value of money because the concept of economic value of time uses profit sharing, while the time value of money uses interest. And its revelance in today’s economy is that in Islamic banking. Islamic recommends always investing money in productive businesses. Invesment in a productive business is at the core of the financial concept according to Islamic sharia. In investing activities, we cannot demand certain income or profits in the future. Because the results of future investments are stongly influenced by many factors, both predictable and unpredictable factors. Factors that can be predicted or calculated in advance such as the amount of capital required, the amount of the agreed ratio, and the level of capital turnover. While the factor that cannot be calculated with certainty is return (investment income). So that the time value of money formulated in the form of interest is not in accordance with Islamic law, the concept of economic value of time emphasizes that it is time that has economic value, not money that has time value.